Social Discourse, Subjectivity and Spatiality in Stephenie Meyer's Twilight: A Model for Interpreting Virginity Narratives - Whyte, Victoria (Université d'Ottawa / University of Ottawa, 2015)
This thesis examines virginity as a social construct, contextualizes the relevance of first sex for contemporary youth, and presents a model for reading themes of virginity and first sex in popular media. Through discursive analysis, the central sections of this thesis – Virginity, Femininity, and Masculinity – analyze themes of sexual abstinence across the four books of the Twilight series. Examining contemporary and historical contexts placing gendered value on virginity and virginity loss, this project suggests that virginity narratives reflect whose bodies are considered to be valuable in society and for what purpose. The conclusion argues that virginity narratives are fundamentally colonial narratives, requiring the fantasy of unclaimed spaces, conquerors, and those to be conquered.
Keywords: virginity; pop culture